2020
DOI: 10.1088/1742-6596/1456/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

A House of Quality (HOQ) matrix of assistive technology for deaf students at elementary school to enhance basic-level language competencies

Abstract: Communication skill is a human basic ability to interact with one another. People usually have no difficulties in communication, yet not for deaf people. The basic communication ability of deaf people tends to be poor due to their hearing impairment. Thus, the technological role is an effective way to enhance communication skill for deaf people or so-called as assistive technology. This study generated a house of quality (HOQ) matrix which can be adopted to develop an assistive technology in the form of langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The literature review has shown that the HoQ method (House of Quality, or QFD -Quality Function Deployment) (Hauser, 1993;Kurniawan, Wijayanti, 2020) is the most often used tool to design and improve products. The idea of HoQ is assumed to be that products should be designed in a way that reflects customer requirements and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review has shown that the HoQ method (House of Quality, or QFD -Quality Function Deployment) (Hauser, 1993;Kurniawan, Wijayanti, 2020) is the most often used tool to design and improve products. The idea of HoQ is assumed to be that products should be designed in a way that reflects customer requirements and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…One particular learning method that has been successful is the Ideal CRV learning method (Mustika et al, 2018). Mirnawati and Yuwono's research (2020) stated that it developed several learning models for students with special needs, one of which was the CRV-IDEAL model which was designed based on the learning principles of deaf children which include face-direction, sound-direction, intersubjectivity, concreteness (Kurniawan & Wijayanti, 2020), visualization (Ratna Ermawaty & Hidayat, 2020, demonstrations, unified experiences, and learning by doing. It is expected to facilitate and make easier for deaf students to participate in class activities, especially for practical courses (Yuwono, 2020).…”
Section: Introductionmentioning
confidence: 99%